Amphibia, Anura, Leptodactylidae, Leptodactylus thomei Almeida and Angulo, 2006: Distribution extension and geographic distribution map - Almeida, A. P.; Gasparini, J. L. (Check List, 2010)
The current study reports the collection of one individual of Leptodactylus thomei at the municipality of Mimosodo Sul, state of Espírito Santo, southeastern Brazil, extending the distribution of this species over 200 Km southwards.